ETHNO-PEDAGOGICAL TOOLS FOR THE FORMATION AND DEVELOPMENT OF NATIONAL PRIDE IN THE TEACHERS (Web of Teachers: Inderscience Research, 2023)
In this article, ethnopedagogical tools aimed at forming and developing a sense of national pride in students today are widely covered. Means of expressing national culture, samples of science, riches of art and literature, traditions and customs of family lifestyle, as well as ethno-pedagogical values, epics are the main means of conveying national pride to the minds of young people.